The Portrait of Children Custody Rights in Indonesia: A Study of Mother's Rights in Child Custody from Gender Perspective - Mohamad Salman Podungge; Siah Khosyi'ah (UIN Sunan Gunung Djati, 2022)
Divorce separates not only husband and wife but also parents and children. After the divorce, the role of the mother is identified as the best caregiver for the child. While the father's role is only limited to providing for the child's needs. The question is